Relation between precision remote sensing and water relations and gas exchange parameters in Verna lemon - Pérez Cutillas P.; Pérez Pérez J.G.; Erena Arrabal M.; Botia Ordaz P.; Robles García J.M.; García Oller M.I.; Montesinos Aranda S. (Drought management: scientific and technological innovations, 2008)
This work is part of the ongoing research being carried out in IMIDA experimental plots for the improvement of irrigation methods used in agriculture in the region of Murcia, contributing significantly to better drought management. Research focused on the correlation of physical variables collected in a plot of citrus trees with data of high-resolution near-infrared images. Values obtained by this correlation help us to automate tasks aimed at estimating the water status of other plots. This study concentrates on minimizing the impact of water shortages in the region of Murcia, which is very sensitive to drought, and on improving the agricultural systems in the region.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)